A FOCUS ON EARLY CHILDHOOD CARE AND EDUCATION TO ENSURE FULFILMENT OF RIGHT TO EDUCATION-2009 - Chopra, Neelima (Innovare Journal of Education, 2015)
With The Dakar Framework for Action, participants of the World Education Forum committed themselves to the achievement of education for all (EFA) goals and targets for every citizen and for every society. For the purpose, they emphasised on the importance of ECCE and adopted the goal of expanding and improving comprehensive early childhood care and education, especially for the most vulnerable and disadvantaged children. India is also a signatory to both the Convention on the Rights of the Child (CRC) 1989 and Education for All (EFA) 1990. Thus, India has long realized the importance of both early years and early childhood education and care. ECCE received attention first time in the National Policy for Children (1974), and later the Integrated Child Development Services (ICDS) was initiated in 1975 with the objective of laying the foundation for holistic and integrated development of child and building capabilities of caregivers. A major step forward was taken when The Right of Children to free and Compulsory Education Act (RTE) which came into effect from April 1, 2010. However, while implementing RTE Act in India, the policy makers left ECCE as an integral component where children below the age of 6 years could also have been benefitted.Â Â A strong foundation of elementary education and issues of availability and accessibility of meaningful education can be built only on a strong foundation of ECCE in the country. This paper therefore attempts to highlight the current status of early childhood educational programmes in Delhi.